From "Expanding Government Influence" to "A Digital Community with a Shared Future" - Agenda-setting Strategies for China's Participation in the Construction of International Institutions in the Digital Space - Yan Li (Athens Journal of Mass Media and Communications)
International agenda setting is the initial and key stage of the creation of international institutions. This paper constructs an analytical framework that includes three elements: institutional platform, agenda setting, means and capabilities. Using methods such as historical institutionalism, text analysis, institutional comparison, and case study, this paper studies the agenda setting strategies in the four paths of China's participation in the construction of international institutions in the digital space. This paper holds that the agenda setting in the four paths has a relationship of inheritance and development, and the autonomy is gradually improved. Specific means of advancing the agenda are limited by institutional platforms; the effect is still not obvious, so the idea should be further improved and the means optimized.